Pemetaan Kualitas Air Tanah Desa Sambibulu Kabupaten Sidoarjo di Area Tempat Penampungan Sampah Sementara - Rahmad Ilham Faidzin; Yayok Suryo Purnomo (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Garbage and water are two important things for human life. Water is one of the natural resources needed by all living things in the world, both humans, animals and plants. Therefore, it must be protected and preserved so that it is not contaminated. One type of pollution is placing garbage close to groundwater sources so that it produces leachate which contaminates the soil. Sidoarjo has a TPS Sambibulu which is a temporary storage area for waste that uses open land because there is no solution to divert it, before finally being disposed of in the Jabon TPA. The location is Jalan Sambibulu, Sambibulu Village, Sidoarjo Regency, East Java 61257. This TPS serves 8,466 people. The average amount of TPS waste is 1024 kg/day, consisting of 39% inorganic waste and 61% organic waste. The purpose of this work is to determine the soil water content in the wells around the TPS with the parameters tested, namely. ammonia (NH3), phosphate (PO), organic matter (KMnO) and groundwater pH at several distances from TPS Sambibulu, and identification. the spread of waste pollution from TPS to groundwater. Based on the results of the study it is known that the majority of pollutant at TPS 0 m, 10 m, 50 m and 100 m exceed PP RI No. 82 of 2001 and PERMENKES RI no. 92/MENKES/PER/IV/2010, but the concentration values of all parameters at a distance of 100 meters from TPS meet the approved quality standards.